OPTIMIZATION OF CREDIT FACILITIES FOR EMPOWERING SMALL AND MICRO ENTERPRISES MODERATED BY FINANCIAL LITERACY - Zulfikry Sukarno; Orfyanny Syahreffy Themba; Susiana Mokhtar (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - The purpose of the study is to analyze and predict the causal relationship of the impact of providing credit facilities to MSEs in Makassar City, in order to maximize their business income. Descriptive quantitative research model with sample determination through non-purposive sampling.METHODOLOGY - . The research sample was 100 Makassar MSE actors who were used as respondents. Data collection from respondent questionnaires. Data analysis uses variant-based SEM to test models and theories. Testing of structural models and measurement models with the help of smartPLS 3.0.FINDING - The test results show that the provision of credit facilities optimally has a significant and positive impact on increasing the business income of MSE actors in Makassar City. Financial literacy owned by MSE actors is able to increase their business income and the role of moderation. Financial literacy does not have an influence on the relationship between credit optimization and MSE empowerment